Top-decision naking bodies of large businesses: Gender quota for supervisory boards is effective - development is almost at a standstill for executive boards - Elke Holst; Katharina Wrohlich (DIW Weekly Report, 2018)
The gender quota for supervisory boards in Germany is effective: by the end of 2017, the proportion of women on the supervisory boards of a good 100 companies that are subject to the quota had risen to 30 percent-three percentage points more than in the previous year. Almost two-thirds of the companies now have supervisory boards with at least 30 percent female members. A European comparison also shows that quota laws work-particularly under the threat of sanctions. So far, there has not been a gender quota introduced for executive boards in Germany. The development of the proportion of women on these boards has almost come to a standstill: of the 200 companies that had generated the most revenue, the proportion of women on each one's executive board at the end of 2017 was around eight percent. In order to bring more women to executive boards and keep them there, it is in their interest for companies to quickly build up and expand their pool of potential female candidates. The next federal government should support this process of reformation by improving general conditions, including strengthening the so far voluntary guidelines for women in high leadership positions.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executive boards; CEOs; women